North Macedonia : Environmental Tax Reform Options and Outcomes - World Bank (World Bank, Washington, DC, 2021)
This paper aims to contribute to the Government’s plans by highlighting key policy options for reforming the tax system to address environmental concerns. It does this through firstly assessing the existing tax system to understand the incentives and measures in place in relation to environmental issues. It then outlines key gaps in the tax system, including in relation to the direction of environmental tax policy globally and in the European Union. As part of this analysis, the paper outlines several policy findings, providing suggested enhancements to the existing fiscal framework to improve environmental performance and support green industries. In doing so, the paper draws from the policy principles that underpin a greening of the tax system, to help guide policy formulation. Indicative impacts of such policy reforms are estimated for key parameters. The paper provides this analysis in the context of the existing policy reforms that are planned and underway, such as the Tax System Reform Strategy (2021-2025), the Strategy for Energy Development of the Republic of North Macedonia until 2040 (October 2019), the Strategy on Environment and Climate Change for the period 2014-2020 (adopted in 2018, developed in 2014), the National Plan for Ambient Air Quality Protection (2012), and the 2017 National Emissions Reduction Plan prepared for commitments under the Energy Community. The paper focuses on the energy sector, specifically on the environmental issues associated with fuel use and how these are influenced by the taxation system. The use of energy, in particular the burning of fossil fuels and fuelwood, is the largest contributor to both greenhouse gas emissions and air pollution in North Macedonia. These have important effects on the environment, human health, and the economy. Reducing emissions from the energy sector is critical to North Macedonia meeting its emissions reduction target of 51 percent below 1990 levels by 2030, set out in its enhanced Nationally Determined Contribution (NDC) under the Paris Agreement. The enhanced NDC along with North Macedonia signing of the Sofia Declaration on the Green Agenda for the Western Balkans3, represents a significant shift in climate policy ambition and appetite for carbon pricing.